POLITICAL EDUCATION FOR PEOPLE TO HAVE AWARENESS AND ACTIVE STANCE IN THE 2024 ELECTION: Pendidikan Politik Agar Masyarakat Memiliki Kesadaran dan Sikap Aktif dalam Pemilu 2024 - Muharram, Fajar; Darmawan Kusuma Wardana, Mahardika; Yulianto, Mochamad Rizal (Journal of Social Comunity Services, 2024)
Political education has a major role in public awareness in having an active attitude towards the participatory democratic process, one of which is elections. Political education is carried out by looking at the typological portrait of Sidoarjo society based on the demography of the region divided into two, namely the type of traditional society and the type of semi-metropolis society. Political education was conducted in five sub-districts of Sidoarjo Regency, namely Jabon, Tanggulangin, Prambon, Tarik and Wonoayu. The implementation of political education to the people of Sidoarjo is done to shape the political personality of Sidoarjo citizens, especially the younger generation, so that it will not lead to apathy or blindness to political issues. In addition, the use of social media is a promising arena and land for conducting political education and political marketing, because it will be directly in contact with two voters who have a large percentage of gadget use.